Pengembangan Video Animasi Berbasis Canva dan Runawawayml "KRIS" (Khulafaur Rasyidin Islamic Stories) pada Pembelajaran PAI Kelas 6 SD - Habibah, Ega Fairuz; Maya, Ginaris; Aeni, Ani Nur (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This article discusses the development of the animated video "KRIS" (Khulafaur Rasyidin Islamic Stories) as a medium for introducing Islamic culture to elementary school students using the Design and Development method. This research aims to provide education to students in elementary schools so that they know and understand Islamic culture, for example by emulating the characteristics of Khulafaur Rasyidin. The animated video "KRIS" received a positive response from users. The evaluation results show that the animated video "KRIS" can increase students' understanding and interest because the design does not get bored. So the animated video "KRIS" can be a very good alternative in learning PAI for grade 6 elementary schools.